Functional Outcomes in Volar-Displaced Distal Radius Fractures Patients with Marginal Rim Fragment Treated by Volar Distal Locking Plates - Naito, Kiyohito; Sugiyama, Yoichi; Kinoshita, Mayuko; Obata, Hiroyuki; Goto, Kenji; Nagura, Nana; Iwase, Yoshiyuki; Obayashi, Osamu; Kaneko, Kazuo (Journal of Hand and Microsurgery, 2019)
Background Treatment of volar-displaced distal radius fractures (DRF) accompanied by marginal rim fragment has recently been actively discussed. It is difficult to obtain a sufficient buttress effect on this fragment. Therefore, we actively apply a distal volar locking plate (DVLP) to fractures with this fragment. Here, we report the treatment outcomes and caveats of surgery of fractures with this fragment.Materials and Methods The subjects were 32 patients (male: 11, female: 21, and mean age: 59.4 years) with volar dislocated DRF accompanied by the marginal rim fragment treated using DVLP. The fracture type of AO classification was B3 in 6 patients, C1 in 12, C2 in 6, and C3 in 8.Results The mean duration of follow-up was 13.8 (12–30) months. The plate could be covered with the pronator quadratus muscle in surgery in all patients. On the final follow-up, visual analog scale score was 1.4/10, quick disabilities of the arm, shoulder, and hand score was 9.2/100, and the Mayo wrist score was 93.7/100. No complication was observed in the soft tissue, such as the nerves and flexor tendons.Conclusion The factor determining retention of the reduction position of the marginal rim fragment is a sufficient buttress effect, and DVLP is a useful implant in terms of this point.
Keywords: distal radius fractures; volar displaced; marginal rim fragment; volar distal locking plates; buttress effect